Effectiveness Test of Local Arbuscular Mycorrhizal Fungi (AMF) and Cocoa Waste Compost on the Growth of Cocoa Seedlings (Theobroma cacao. L) in Former Mining Sites - Meisilva erona sitepu; Doni Hariandi; Tiara Septirosya (Department of Crop Science, Faculty of Agriculture, Andalas University, 2024)
There is ample opportunity for cocoa (Theobroma cacao L.) plantations because the world demand for cocoa increases every year. Cocoa plants bear fruit every year without knowing the season so cocoa cultivation provides promising prospects. The demand for cocoa must be balanced with increased in production from the cultivation scale from providing seeds to expanding cocoa planting land. The experimental design used in this study was a two-factor Randomised Group Design, namely the provision of AMF F0 (without AMF) and F1 (with AMF). The second factor is cocoa waste compost in planting media (v/v) with five levels, namely k0 (0%), k1 (5%), k2 (10%), k3 (15%),and k4 (20%). The aim of the research was to see the effectiveness of AMF and cocoa waste compost on the growth of cocoa seedling. Based on the research results, it can be concluded that the treatment of FMA can increase plant height, root volume, root dry weight, and percentage of colonized roots. Cocoa seedlings gave the best response with a dose of 0% cocoa waste compost with AMF treatment, with an average height of 60.19 cm . The percentage of AMF colonization is high at 44.6%. The final soil analysis showed an increase in P-available pH and soil Ald with mycorrhiza and cocoa shell compost treatment at a dose of 10%